Genome sequencing and analysis of Salmonella enterica subsp. enterica serovar Stanley UPM 517: insights on its virulence-associated elements and their potentials as vaccine candidates - Ashari, Khalidah Syahirah; Roslan, Najwa Syahirah; Omar, Abdul Rahman; Bejo, Mohd Hair; Ideris, Aini; Mat Isa, Nurulfiza (PeerJ, 2019)
Salmonella enterica subsp. enterica serovar Stanley (S. Stanley) is a pathogen that contaminates food, and is related to Salmonella outbreaks in a variety of hosts such as humans and farm animals through products like dairy items and vegetables. Despite the fact that several vaccines of Salmonella strains had been constructed, none of them were developed according to serovar Stanley up to this day. This study presents results of genome sequencing and analysis on our S. Stanley UPM 517 strain taken from fecal swabs of 21-day-old healthy commercial chickens in Perak, Malaysia and used Salmonella enterica subsp. enterica serovar Typhimurium LT2 (S. Typhimurium LT2) as a reference to be compared with. First, sequencing and assembling of the Salmonella Stanley UPM 517 genome into a contiguous form were done. The work was then continued with scaffolding and gap filling. Annotation and alignment of the draft genome was performed with S. Typhimurium LT2. The other elements of virulence estimated in this study included Salmonella pathogenicity islands, resistance genes, prophages, virulence factors, plasmid regions, restriction-modification sites and the CRISPR-Cas system. The S. Stanley UPM 517 draft genome had a length of 4,736,817 bp with 4,730 coding sequence and 58 RNAs. It was discovered via genomic analysis on this strain that there were antimicrobial resistance properties toward a wide variety of antibiotics. Tcf and ste, the two fimbrial virulence clusters related with human and broiler intestinal colonizations which were not found in S. Typhimurium LT2, were atypically discovered in the S. Stanley UPM 517 genome. These clusters are involved in the intestinal colonization of human and broilers, respectively. There were seven Salmonella pathogenicity islands (SPIs) within the draft genome, which contained the virulence factors associated with Salmonella infection (except SPI-14). Five intact prophage regions, mostly comprising of the protein encoding Gifsy-1, Fels-1, RE-2010 and SEN34 prophages, were also encoded in the draft genome. Also identified were Type I–III restriction-modification sites and the CRISPR-Cas system of the Type I–E subtype. As this strain exhibited resistance toward numerous antibiotics, we distinguished several genes that had the potential for removal in the construction of a possible vaccine candidate to restrain and lessen the pervasiveness of salmonellosis and to function as an alternative to antibiotics.